A composite superconducting energy pipeline and its characteristics. (November 2022) - Jin, Jianxun; Wang, Lina; Yang, Ruohuan; Zhang, Tianlong; Mu, Shuai; Zhou, Qian
Abstract: A superconducting energy pipeline cooled during its clean energy transferring becomes attractive recently to be a promising alternative way for combined green energy transmission to meet the ever-rising energy demand across the world. Though, study on superconducting energy pipelines gets into the conceptual design of single energy integration, the critical multi-composite structure and its characteristics have not yet been systematical. A novel high-temperature superconducting (HTS) energy pipeline integrated with power cable and liquid hydrogen (LH2 ) and liquefied natural gas (LNG) is proposed in this paper. The maximum allowable temperature difference and pressure drop methods are adopted to design the pipeline. A two-dimensional axisymmetric electromagnetic thermal coupling model has been established using the finite element method. The interface magnetic field formulation, heat transfer modeling, and multiphysics interface has been applied to conduct a detailed analysis of the designed superconducting energy pipeline (LH2 -LNG-HTSEP). The results show that the designed LH2 -LNG-HTSEP is feasible for practical operation and has more favorite characteristics to suit the HTS cable for the composite pipeline operation. The model and analysis method provide a theoretical base for the composite superconducting energy pipeline design and structural optimization.